2014
DOI: 10.1016/j.cmet.2014.04.003
|View full text |Cite
|
Sign up to set email alerts
|

α/β-Hydrolase Domain-6-Accessible Monoacylglycerol Controls Glucose-Stimulated Insulin Secretion

Abstract: Glucose metabolism in pancreatic β cells stimulates insulin granule exocytosis, and this process requires generation of a lipid signal. However, the signals involved in lipid amplification of glucose-stimulated insulin secretion (GSIS) are unknown. Here we show that in β cells, glucose stimulates production of lipolysis-derived long-chain saturated monoacylglycerols, which further increase upon inhibition of the membrane-bound monoacylglycerol lipase α/β-Hydrolase Domain-6 (ABHD6). ABHD6 expression in β cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
180
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 143 publications
(193 citation statements)
references
References 55 publications
12
180
1
Order By: Relevance
“…Another likely lipid candidate is monoacylglycerol. We have recently shown that monoacylglycerol stimulates basal insulin secretion, and Zhao et al have shown that it binds the exocytotic protein Munc13-1 (32,56). Another possibility is that a change in the lipid composition of the plasma membrane may alter the Ca 2ϩ threshold needed for GSIS and thus shift the dose-response curve.…”
Section: Discussionmentioning
confidence: 99%
“…Another likely lipid candidate is monoacylglycerol. We have recently shown that monoacylglycerol stimulates basal insulin secretion, and Zhao et al have shown that it binds the exocytotic protein Munc13-1 (32,56). Another possibility is that a change in the lipid composition of the plasma membrane may alter the Ca 2ϩ threshold needed for GSIS and thus shift the dose-response curve.…”
Section: Discussionmentioning
confidence: 99%
“…After transfection using Lipofectamine, INS832/13 cells were cultured for 48 h in 96-well, 12-well, or 6-well plates. siRNAs against G3PP and two scrambled siRNAs were introduced into INS832/13 cells by RNAiMAX (40). Transfected cells were used for Western blotting and measurements of insulin secretion, caspase activity, glycerol and FFA release, O 2 consumption, and fatty acid oxidation and esterification.…”
Section: Methodsmentioning
confidence: 99%
“…These include a glycerolipid/ free fatty acid cycle (15), which generates monoacylglycerol as a coupling factor (16); a phosphoenolpyruvate and mitochondrial GTP-dependent pathway (17,18); and so-called "pyruvate cycles" (19)(20)(21), which export reducing equivalents from the mitochondria to the cytosol. The mitochondrial export of citrate and isocitrate and subsequent engagement of isocitrate with the cytosolic NADP + -dependent isocitrate dehydrogenase (IDH1, hereafter referred to as ICDc) has been shown to regulate insulin secretion (22,23), but the metabolites generated by this pathway that engage with the Insulin secretion from β cells of the pancreatic islets of Langerhans controls metabolic homeostasis and is impaired in individuals with type 2 diabetes (T2D).…”
Section: Introductionmentioning
confidence: 99%